Development of PU Coatings from Neem Oil Based Alkyds Prepared by the Monoglyceride Route. (24th April 2015) - Chaudhari, Ashok; Kulkarni, Ravindra; Mahulikar, Pramod; Sohn, Daewon; Gite, Vikas
Abstract: This work deals with the preparation of alkyd resins from neem oil and their utilization in preparation of polyurethane coatings. Alkyd resins were synthesized by reaction of neem oil monoglycerides with four different divalent acids like phthalic anhydride, maleic anhydride, itaconic acid, and dimer fatty acid. The alkyds formation was studied by determining the acid number of the reaction mixture at regular intervals of time and the extents of the polyesterification reactions were calculated during the formation of alkyds. The structures of synthesized alkyds were confirmed by FT‐IR and 1 H‐NMR spectroscopic analysis and also by end group analysis such as hydroxyl and acid values. The synthesized alkyds were reacted with TDI to prepare PU coatings and their performance was compared with PU coatings prepared from a commercial alkyd.